Molecular Mechanisms Associated With Particulate and Soluble Heteroglycan Mediated Immune Response. Issue 7 (7th December 2015) - Devi, K. Sanjana P.; Krishna, Dhanesh; Das, Joyjyoti; Agarwal, Tarun; Kumari, Kalpana; Maji, Somnath; Ghosh, Sudip K.; Maiti, Tapas K.
ABSTRACT: Immune responses are outcomes of complex molecular machinery which occur inside the cells. Unravelling the cellular mechanisms induced by immune stimulating molecules such as glycans and determining their structure‐function relationship are therefore important factors to be assessed. With this viewpoint, the present study identifies the functional receptor binding unit of a well characterized heteroglycan and also delineates the cellular and molecular processes that are induced upon heteroglycan binding to specific cell surface receptors in immune cells. The heteroglycan was acid hydrolysed and it was revealed that 10–30 kDa fractions served as the functional receptor binding unit of the molecule. Increasing the size of 10–30 kDa heteroglycan showed prominent immune activity. The whole soluble heteroglycan was also conjugated with hyperbranched dendrimers so as to generate a particulate form of the molecule. Dectin‐1 and TLR2 were identified as the major receptors in macrophages that bind to particulate as well as soluble form of the heteroglycan and subsequently caused downstream signaling molecules such as NF‐κβ and MAPK to get activated. High levels of 1L‐1β and IL‐10 mRNA were observed in particulate heteroglycan treated macrophages, signifying that increasing the size and availability of the heteroglycan to its specific receptors is pertinent to its biological functioning. Upregulated expression of PKC and iNOS were also noted in particulate heteroglycan treated RAW 264.7 cells than the soluble forms. Taken together, our results indicate that biological functions of immunomodulatory heteroglycan are dependent on their size and molecular weight. J. Cell. Biochem. 117: 1580–1593, 2016. © 2015 Wiley Periodicals, Inc. Abstract : Size and molecular weight are key governing factors of heteroglycan induced immune response. NF‐κβ and MAPK cascade gets activated on heteroglycan binding to Dectin‐1 and TLR2 receptors in macrophages, following which a gamut of immune effector molecules get synthesized.